Pengaruh Model Pembelajaran Creative Problem Solving Terhadap Kemampuan Pemecahan Masalah Peserta Didik Fase F Materi Pengangguran - Meisyarah Diva; Marwan (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
The purpose of this study was to identify the effect of the application of the Creative Problem Solving (CPS) model on the problem-solving thinking skills of Phase F students on unemployment material at SMA Negeri 3 Payakumbuh. This study used a quasi-experimental approach with a pretest–posttest control group design, involving 68 grade XI students who were divided into experimental and comparison groups. Data were collected through problem-solving ability tests and processed descriptively and quantitatively with non-parametric difference tests, which showed significant differences in problem-solving abilities between students who learned with the CPS model and those who used traditional methods. The results of this study are expected to contribute to the development of more innovative and effective learning strategies in the school environment. In addition, these findings can also be a reference for educators in improving the quality of the learning process, especially in training students' critical thinking and problem-solving skills optimally.